1990
DOI: 10.1007/bf01643436
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic chemotherapy with fosfomycin trometamol during transurethral surgery and urological manœuvres. Results of a multicentre study

Abstract: The aim of the present open prospective study is to evaluate the efficacy and safety profile of fosfomycin trometamol in the chemoprophylaxis of urinary tract infections following transurethral diagnostic and/or therapeutic manoeuvres. 712 patients were enrolled in 72 urological surgical centres. All the enrolled patients received an initial dose of fosfomycin trometamol (Monuril sachet containing 3 g of active drug in powder) 3 h before and a second dose 24 h after the transurethral manoeuvres. Clinical and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In a report, 23 bacterial adhesion to the bladder tumor caused postoperative UTIs, even if the preoperative urine was sterile, and the incidence of UTIs after TUR‐Bt was higher than that after TUR‐P. Therefore, AMP is recommended to prevent UTIs after TUR‐Bt 19,20,24–28 . Most strains isolated from UTIs after TUR‐Bt were Gram negatives 22,25,27 .…”
Section: Detailed Expositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report, 23 bacterial adhesion to the bladder tumor caused postoperative UTIs, even if the preoperative urine was sterile, and the incidence of UTIs after TUR‐Bt was higher than that after TUR‐P. Therefore, AMP is recommended to prevent UTIs after TUR‐Bt 19,20,24–28 . Most strains isolated from UTIs after TUR‐Bt were Gram negatives 22,25,27 .…”
Section: Detailed Expositionmentioning
confidence: 99%
“…Therefore, AMP is recommended to prevent UTIs after TUR‐Bt 19,20,24–28 . Most strains isolated from UTIs after TUR‐Bt were Gram negatives 22,25,27 . However, the distribution of streptococci from postoperative UTIs in female patients was reported to be high 29 .…”
Section: Detailed Expositionmentioning
confidence: 99%
“…The largest trial [14] was conducted as an open study in 72 urological surgical centers in Italy on 712 (mainly male) patients undergoing different transurethral interventions, i.e. surgical procedures, such as TURP (31.2%) and TURB (19.5%), in 53.5% of the patients and other endoscopic (mainly diagnostic) procedures in 46.5% of the patients, such as cystoscopy (38.9%), urodynamic studies (5.5%), lithotripsy (2.1%) and urethrotomy (2.8%).…”
Section: Ft For Pap In Endourological Interventions and Surgical Procmentioning
confidence: 99%
“…The fact that it is directly extracted through the urine without being metabolized in the body strongly suggested that transurethral administration of FOF would be more beneficial than the oral application to a certain extent 17. A number of studies have reported on the use of fosfomycin for prophylactic purposes in patients before surgical interventions 1823. Among these, the ones employing prophylactic oral FOF administration reported infection prevention success as 88.6% to 100% following transurethral resection of the prostate and urological interventions for diagnostic or treatment purposes 20.…”
Section: Discussionmentioning
confidence: 99%